Assistance on Writing Scientific Papers for Students of Nusaniwe Village - Godprit Haris Touwely; Resa Dandirwalu; Maya Laisila; Ricardo Freedom Nanuru (Indonesian Journal of Cultural and Community Development, 2019)
Nusaniwe Student Association (IKAMAPENUSA) in Ambon City is an organization formed on the initiative of several educational figures from Negeri Nusaniwe (in Ambon City; the village is referred to as Negeri) with the aim of helping to develop the role of students in developing themselves, both in terms of academics and organizations. Observing the dynamics of plagiarism among students, the Stimulus Community Partnership Program (PKMS) team from Indonesia Christian University (UKIM) of Maluku, Ambon, took the initiative to approach IKAMAPENUSA to discuss issues related to their assignments as students. From the results of the discussion, it appears that there are a lot of problems they face, for example: (1) Lack of direction from teachers and lecturers related to the tasks assigned; (2) Lack of knowledge on how to look for good, well-categorized scientific literature; (3) lack of mastery of paraphrasing techniques; (4) lack of mastery of scientific writing techniques required by universities and schools; (5) Lack of mastery of technology related to quotations and bibliography such as Mendeley. The output of this activity has been published in Mimbar Rakyat News electronic mass media (http://mimbarrakyatnews.com/tim-pkms-ukim-gelar-penulisan-karya-ilmiah-bebas-plagiat-2/), and the video of activities has been uploaded to YouTube channel of UKIM TV (https://www.youtube.com/watch?v=tg-Cqn0-zao).